Effect of yohimbine on reinstatement of operant responding in rats is dependent on cue contingency but not food reward history - Chen, Yu-Wei (Addict Biol, 2014)
Yohimbine is an alpha-2 adrenoceptor antagonist that has been used in numerous studies as a pharmacological stressor in rodents, monkeys, and humans. Recently, yohimbine has become the most common stress manipulation in studies on reinstatement of drug and food seeking. However, the wide range of conditions under which yohimbine promotes reward seeking is significantly greater than that of stressors like intermittent footshock. Here we addressed two fundamental questions regarding yohimbine’s effect on reinstatement of reward seeking: (1) whether the drug’s effect on operant responding is dependent on previous reward history or cue contingency, and (2) whether yohimbine is aversive or rewarding under conditions typically used in reinstatement studies. We also used in vivo microdialysis to determine yohimbine’s effect on dopamine levels in nucleus accumbens (NAc) and medial prefrontal cortex (mPFC). We found that the magnitude of yohimbine-induced (0.5, 1.0, 2.0 mg/kg) operant responding during the reinstatement tests was critically dependent on the contingency between lever-pressing and discrete tone-light cue delivery but not the previous history with food reward during training. We also found that yohimbine (2 mg/kg) did not cause conditioned place aversion. Finally, we found that yohimbine modestly increased dopamine levels in mPFC but not NAc. Results suggest that yohimbine’s effects on operant responding in reinstatement studies are likely independent of the history of contingent self-administration of food or drug rewards and may not be related to the commonly assumed stress-like effects of yohimbine.